PEMBINAAN KARAKTER MELALUI PEMBELAJARAN TARI DI SMP NEGERI 35 PADANG - Aulya, Vinna; Astuti, Fuji (SENDRATASIK UNP, 2019)
AbstractÂ This article aims to describe the character development through dance learning at SMP N 35 Padang. The research was a qualitative research with a descriptive approach. This research was conducted in IX grade which amounted to 24 students. The main research instrument was the reseracher herself and assisted by supporting tools such as stationeries and photo camera. Character Education is the education that places great emphasis on the aspect of values that are expected to produce human the have a high sensitivity to the upholding of the values of truth, justice, humanity and progress which are the foundation in human life on this earth. Based on interviews with arts and culture teacher (on July 6, 2018) and several teachers at SMP N 35 Padang, they stated that the students at the school prefered to be busy with their own activities, even they had deviant behavior.The results of this study indicated that through dance students' characters emerged, these studentsâ€™ characters were divided into three namely; appearing, some appearing and not appearing in the students. Then, the 8 characters that appeared in the students are religious, honest, tolerance, respect for achievement, friendship, love for peace, social care and the environment.The 6 other characters partly appeared in the students, namely curiosity, discipline, hard work, independent, responsibility, creative. Meanwhile, the 4 characters that did not appear at all in the formation of character through dance were the spirit of nationalism, love of the motherland, and fond of reading.Based on the description above, it could be concluded that dance could be a media in shaping Character Building through Dance Learning because there were 8 characters that appeared in each students. Keywords: character building, dance art, dance education